2005
DOI: 10.1590/s1806-37132005000700006
|View full text |Cite
|
Sign up to set email alerts
|

Anticorpos contra o citoplasma de neutrófilos

Abstract: 31(Supl 1):S16-S20Radu AS, Levi M S 16 As vasculites sistêmicas são um grupo de doenças raras. Seu diagnóstico representa um desafio clínico de grande importância, pois permite um tratamento precoce e direcionado para estas situações potencialmente graves. Da mesma forma, o acompanhamento evolutivo destas patologias depende de dados clínicos e/ou laboratoriais que permitam diferenciar atividade de remissão. No entanto, o quadro clínico inicial das vasculites é comumente inespecífico, exigindo a espera de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…These antibodies are immunoglobulins against azurophil granules containing many different proteins, such as myeloperoxidase (MPO), elastase, proteinase 3 (PR3), and cathepsin G, among others. 7 , 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies are immunoglobulins against azurophil granules containing many different proteins, such as myeloperoxidase (MPO), elastase, proteinase 3 (PR3), and cathepsin G, among others. 7 , 15…”
Section: Discussionmentioning
confidence: 99%
“…If the antibodies target Proteinase 3, they are known as C-ANCA, because they exhibit a central cytoplasmic staining pattern. 7 , 15…”
Section: Discussionmentioning
confidence: 99%
“…Se dois dos seguintes achados: inflamação oral ou nasal, nódulos ou opacidades na radiografia de tórax, hematúria microscópica, inflamação granulomatosa na biópsia da parede de vasos e a presença do anticorpo Anti Citoplasma de Neutrófilos (ANCA-c) positivo forem encontrados, tem-se até 90% de especificidade. Porém, outras doenças da classe das vasculites sistêmicas também apresentam o ANCA-c positivo (6). Vale ressaltar, que os sintomas iniciais da GW são praticamente inespecíficos, o que não permite sua diferenciação em estágios iniciais.…”
Section: Introductionunclassified
“…Therefore, screening for the presence of these antibodies should always be performed by immunofluorescence, ELISA being reserved for special cases. (8) In AAV, pulmonary manifestations occur especially in WG. A study conducted in Brazil and involving 98 patients (mean age, 48 ± 15 years) with WG who were recruited from a department of pulmonology, which represents a bias, revealed that 98% of the cases had pulmonary involvement, characterized by (cavitary or noncavitary) pulmonary nodules, (cavitary or noncavitary) masses, pulmonary consolidations, ground-glass areas (commonly associated with alveolar hemorrhage), and lower airway injury (subglottic stenosis, tracheal stenosis, bronchial stenosis, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it should be emphasized that not every form of AAV shows this marker and not every ANCA-positive patient has vasculitis. (8) Immunofluorescence is the primary technique for the study of ANCA. With this method, it is possible to observe two patterns closely related to the presence of clinically evident vasculitis: cytoplasmic ANCA (c-ANCA), present in 80% of cases of WG and in 30% of cases of MPA, and perinuclear ANCA (p-ANCA), present in 10% of cases of WG and in 60% of cases of MPA.…”
Section: Introductionmentioning
confidence: 99%